2012
DOI: 10.1136/bmjqs-2012-001102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of traditional trigger tool to data warehouse based screening for identifying hospital adverse events

Abstract: We found relatively poor agreement between traditional trigger tool and EDW based screening with only approximately a third of all AEs detected by both methods. A combination of complementary methods is the optimal approach to detecting AEs among hospitalised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
62
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 29 publications
0
62
0
Order By: Relevance
“…“Abrupt medication stop” was a criterion in five studies; one [23] specified this for an enterprise data warehouse query as “discontinuation of 4 of more medications in a 6 h period >48 h after admission and at least 24 h prior to discharge”.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…“Abrupt medication stop” was a criterion in five studies; one [23] specified this for an enterprise data warehouse query as “discontinuation of 4 of more medications in a 6 h period >48 h after admission and at least 24 h prior to discharge”.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies used automated methods: one compared automated with traditional manual triggers [23] and another electronically screened discharge summary text [41]. These did not report proportion of errors that were diagnostic in nature.…”
Section: Resultsmentioning
confidence: 99%
“…Including an economic dimension to the knowledge gained from research into quality and safety is an important part of the health system reform that is being implemented in Portugal [5,12,29,30]. Moreover, it could be a starting point for specific interventions in the improvement of patient safety and it may help to prioritise research areas for the near future [6,20,27,31]. …”
Section: Discussionmentioning
confidence: 99%
“…We observed that the quality of patient records could be better, although this did not significantly limit the study. Retrospective patient record studies still represent the “gold-standard” method for assessing incidence and monitoring the frequency of AEs [13,20,31,32] and the use of similar methods to those used elsewhere allows comparisons to be made. However, for a more comprehensive assessment of safety, other methods also need to be used, including reporting and learning systems, root-cause analyses, failure mode effects analyzes and morbidity and mortality reviews [13,33].…”
Section: Discussionmentioning
confidence: 99%
“…We used a modified version of the classic 2-stage method to identify and confirm AEs. 2 In the first stage, we used computerized screens, based on criteria from the Harvard Medical Practice Study and Institute for Healthcare Improvement global trigger tool, to identify potential AEs. [3][4][5] A research nurse created narrative summaries of potential AEs.…”
mentioning
confidence: 99%